"I am like a green olive tree": The Wisdom context of Psalm 52 - Botha, Philippus J. (HTS teologiese studies, 2013)
The article revisits the thesis of Walter Beyerlin from 1980 that Psalm 52 is a paraenetic- didactic Wisdom poem from the late Persian period. Beyerlin reached his conclusion from a comparison of Psalm 52 with post-exilic Wisdom psalms such as Psalms 37, 49, and 73. The direct literary influence that Psalm 52 received from the book of Proverbs and the motifs it shares with Jeremiah 9 are investigated here, since the author contends that the Wisdom influence on the Psalm was even greater than Beyerlin had envisaged. The article comes to the conclusion that the author(s) of the Psalm attempted to compose a psalm by establishing a network of allusions to a corpus of authoritative texts, inter alia, the Wisdom psalms. The end product is a brilliant composition which interprets the teaching of Proverbs for the needs of a group of Jewish believers who probably lived at the end of the Persian period.